Prevalence and Correlates of Disability Among a Sample of Victimized Women on Probation and Parole. (April 2019) - Smith, Kirsten E.; Bunting, Amanda M.; Golder, Seana; Hall, Martin T.; Higgins, George E.; Logan, T. K.
The purpose of this exploratory study was to establish the prevalence of disability as measured by self-reported Social Security Disability Insurance (SSDI) receipt among a sample of women on probation and parole who have experienced interpersonal victimization in childhood and/or adulthood. Women receiving SSDI were more likely to be older, White, to live alone, and to score lower on measures of social support compared to women not receiving SSDI. SSDI recipients were also more likely to report poorer health, chronic pain, and more frequent health care service utilization. High rates of adverse childhood experiences, rape, adult victimization, and an overall greater severity of post-traumatic stress disorder symptomatology were observed for women receiving SSDI. Groups had similar overall mental health profiles and diverged primarily on trauma variables. Findings support the need for trauma-informed care and highlight the possibility that some criminal justice system–involved women likely qualify for SSDI, yet are not receiving it.